The limitations of school - Brown, Sparkhall (Statistical and Social Inquiry Society of Ireland, 1919)
During the past two years two papers on Educational topics have been read to this Society, one by Mr. Williamson entitled "Post-War Functions of Commercial Education," and the other by Mr. Ryan on "The Preparation of National School Pupils for Technical Training and Industrial Life." My excuse for bringing the subject again under the notice of the Society is, first that both these papers dealt with special aspects of Education, whereas I propose to treat the subject more as a whole, and, second, that at the present moment the subject of education is one of especial interest.
Read Friday May 24th, 1918
Keywords: Limitations of teaching; Curriculum; 314.15